Desain dan Pengembangan Robot Monitoring Keamanan Berbasis Internet of Things dengan Dukungan Transmisi Video Real-Time Menggunakan ESP32-CAM - Theofilus Herly Hatonangan Samosir; Layli Ana (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Security is a crucial aspect in protecting homes, offices, and warehouses from potential intrusions and theft. Conventional surveillance systems using static CCTV cameras are limited in that they can only monitor a specific area and cannot move to cover unobserved areas. This research aims to design and build an Internet of Things (IoT)-based security monitoring robot using an ESP32-CAM with real-time video transmission. The developed system consists of an ESP32-CAM as a microcontroller and camera module, an L298N Motor Driver Module, two DC motors, a robot chassis, and a battery as a power source. The robot is controlled through a web interface accessible using a smartphone or laptop via a Wi-Fi network. The ESP32-CAM's camera displays a real-time video stream, allowing users to monitor environmental conditions and control the robot's movements in various directions. The research method used was Research and Development (R&D), which included literature review, requirements analysis, hardware and software design, system implementation, and data testing and analysis. Test parameters included the success of the robot's motion control, video streaming quality, system response time, and Wi-Fi connection range. The research results are expected to demonstrate that the system is capable of displaying real-time video and controlling the robot with good responsiveness. This prototype could be an effective, flexible, and economical security monitoring solution.